The Role of Artificial Intelligence in the Future of Language Teaching and Learning Practices in Higher Education - Job W. Mwakapina (Pan-African Journal of Education and Social Sciences)
Integrating Artificial Intelligence (AI) into education is set to transform teaching and learning practices. Although the benefits of AI in education are vast, significant challenges and uncertainties persist. This study examines the role of AI in language teaching and learning at a university in Tanzania, focusing on its applications, impacts, challenges, and ethical considerations. Data were collected from 128 participants through surveys, interviews, observations, and group discussions. The findings revealed the growing use of AI-powered educational technologies in Tanzanian university settings, offering innovative solutions to traditional challenges and optimizing learning outcomes. However, challenges such as data privacy, lack of proficiency in AI, lack of suitable equipment, plagiarism issues, and high dependency on AI need to be addressed. Moreover, questions about the evolving roles of teachers and the ethical implications of AI usage in education. Despite the challenges, the study highlights AI’s potential to transform teaching, personalize learning, and enhance instruction through improved access to materials and data analysis. Furthermore, instructors mainly benefit from AI lesson content creation and virtual reality simulations. Concerns regarding dependency and misuse raise issues regarding critical thinking and integrity. This study advocates for ongoing dialogue among stakeholders to ensure responsible AI integration and maximize its benefits.